Kendala Implementasi Manajemen Talenta Polri Dalam Pengembangan Karier Anggota Di Polda Jawa Barat - Samosir, M. Rido Pratama (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study analyzes the obstacles in implementing the Indonesian National Police (Polri) Talent Management in supporting career development of police personnel at West Java Regional Police (Polda Jabar). The background is the importance of superior human resources in Polri in the modern era, contrasted with indications that the Polri Talent Management Program (MTP), implemented since 2017, has not run optimally in some regions. The research method is descriptive qualitative with a case study approach at Polda Jabar, utilizing field observations and supporting quantitative data analysis. The results show several key obstacles: (1) inconsistent and formalistic execution of MTP – for example, some mentors do not fully understand their talent development duties; (2) limited integration of MTP with formal career development systems such as advanced leadership education, evidenced by the low proportion of talent officers who get the opportunity to attend required career advancement schooling; and (3) resource and commitment factors, including limited training quotas and lack of regular monitoring by leadership, contributing to MTP’s ineffectiveness. These findings indicate that Polri Talent Management at Polda Jabar has not yet effectively facilitated personnel career development as intended. The study recommends improving mentor capacity and understanding, aligning MTP with promotion and advanced education processes, and strengthening organizational support so that MTP can function optimally.